2016
DOI: 10.1080/09613218.2016.1222190
|View full text |Cite
|
Sign up to set email alerts
|

Overheating in vulnerable and non-vulnerable households

Abstract: As the 2003 European heat wave demonstrated, overheating in homes can cause wide scale fatalities. With temperatures and heat wave frequency predicted to increase due to climate change, such events can be expected to become more common. Thus, investigating the risk of overheating in buildings is key to understanding the scale of the problem and in designing solutions. Most work on this topic has been theoretical and based on lightweight dwellings that might be expected to overheat. By contrast, in this study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 41 publications
(66 reference statements)
5
45
1
Order By: Relevance
“…A number of other factors besides air temperature have been identified to influence window operation 54 . In addition, it has been demonstrated that people perceive indoor temperatures and act to change their thermal comfort differently 9,55 . Two other implicit assumptions that fundamentally relate to the binary nature of the assessment and are not addressed in the guidance document are that: (a) the uncertainty of BPS tools and (b) the choice of BPS tool will not significantly alter the prediction.…”
Section: Tm59 Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other factors besides air temperature have been identified to influence window operation 54 . In addition, it has been demonstrated that people perceive indoor temperatures and act to change their thermal comfort differently 9,55 . Two other implicit assumptions that fundamentally relate to the binary nature of the assessment and are not addressed in the guidance document are that: (a) the uncertainty of BPS tools and (b) the choice of BPS tool will not significantly alter the prediction.…”
Section: Tm59 Methodologymentioning
confidence: 99%
“…A meta-analysis estimated that currently 30% of the world's population is experiencing extreme levels of heat, a figure that may rise to 70% by 2100 if no action is taken to tackle climate change 7 . This would place the elderly and vulnerable (disabled or with long-term illnesses) most at risk 4,8,9 . To tackle these and other potential effects of climate change, international agreements aimed at reducing global carbon emissions have been negotiated 10 .…”
Section: Introductionmentioning
confidence: 99%
“…33 The static overheating criteria and mean monitored temperatures over the summer period were used to determine whether significant differences exist due to location, external wall type, age band and building type. However, as suggested by the literature, 27,32,33 numerous other factors could influence the indoor environment. In addition, as the distribution of characteristics (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reproduced from Symonds et al 41 assess overheating risk in previous in-use studies. 27,30,42 A high risk of indoor overheating was assumed if either of the following thresholds is exceeded: 20 1. The percentage of occupied hours where the operative temperature (T op ) exceeds the maximum allowable temperature (T max ) by 1 C or more during the period May to September, inclusive, should not exceed 3%.…”
Section: Indoor Overheating Assessmentmentioning
confidence: 99%
“…In the UK, 20% of households may already be at risk of overheating [15], and, with the predicted climate change, this percentage will likely increase [4]. Although no universal definition of overheating exists, the phenomenon has been widely monitored [15][16][17][18][19][20][21][22][23][24], and thermally modelled [25][26][27][28][29][30] using either static or adaptive assessment criteria. Numerous studies have examined a number of dwelling types that represent broadly the housing stock in the UK.…”
Section: Introductionmentioning
confidence: 99%